DETERMINAN KINERJA ANGGARAN BERBASIS VALUE FOR MONEY PADA SEKTOR PUBLIK (Studi pada SKPD Aceh Tamiang) - Puspita Sari; Nurlaila Hanum; Muhammad Salman (Jurnal Mahasiswa Akuntansi Samudra, 2021)
This study aims to determine the effect of accountability, timeliness and internal control on value for money-based budget performance in the public sector (study on SKPD Aceh Tamiang). The population of this study are people who are involved in budgeting and understand the budget at the Aceh Tamiang SKPD as many as 32 SKPD. The sampling technique used the Saturated Sample method where all SKPDs were sampled. Data were collected by distributing questionnaires to 96 respondents. The data obtained were then analyzed using SPSS (Statistical Package for the Social Sciences). The results showed that simultaneously the variables of accountability, timeliness, and internal control had a significant effect on value for money-based budget performance. While partially shows that the variables of accountability and internal control have a significant influence on the performance of the value for money-based budget. While the timeliness variable has no effect on value for money based budget performance.